Accelerated corrosion performance of solar cells: A critical review - Jimenez-Arevalo, V; Jimenez-Arevalo, V (Elsevier B.V., 2026)
Accelerated corrosion is a key determinant of photovoltaic system degradation, particularly in environments with high moisture content and salt-exposed environments. This review explores a critical synthesis of accelerated corrosion mechanisms in solar cells, highlighting the impact of atmospheric exposure, salt ingress, and moisture penetration on material degradation. Salt spray chamber testing, based on ASTM standards, is discussed as a key method for simulating corrosion. Electrochemical techniques, including potentiodynamic polarization and electrochemical impedance spectroscopy (EIS), are explored for their capacity to quantify corrosion kinetics and detect early-stage degradation. Morphological and structural analyses (SEM, AFM, XPS, FTIR) identify critical defects, including delamination, snail trails, and metallization discoloration (ribbon). These defects reduce electrical performance and optical efficiency. This review aims to discuss generational changes in materials and designs to enhance corrosion resistance. Propose a multidimensional framework for real-time monitoring and failure prediction. These insights are crucial to the development of robust PV technologies, particularly for deployment in extreme climates. This work connects ASTM-B117 salt spray testing with electrochemical and nanoscale characterization, providing a unique framework to explain corrosion in solar cells. This integrated approach highlights ribbon and interconnect corrosion across PV generations and proposes strategies to enhance durability. © © 2025. Published by Elsevier B.V.